Cytotoxicity Effect of Iron Oxide (Fe3O4)/Graphene Oxide (GO) Nanosheets in Cultured HBE Cells - Zhang, Yule; Zhang, Yatian; Yang, Zhijin; Fan, Yan; Chen, Mengya; Zhao, Mantong; Dai, Bo; Zheng, Lulu; Zhang, Dawei (Frontiers in Chemistry, 2022)
Iron oxide (Fe3O4), a classical magnetic material, has been widely utilized in the field of biological magnetic resonance imaging (MRI). Graphene oxide (GO) has been also extensively applied as a drug carrier due to its high specific surface area and other properties. Recently, numerous studies have synthesized Fe3O4/GO nanomaterials for biological diagnosis and treatments, including photothermal therapy and magnetic thermal therapy. However, the biosafety of the synthesized Fe3O4/GO nanomaterials still needs to be further identified. Therefore, this research intended to ascertain the cytotoxicity of Fe3O4/GO after treatment with different conditions in HBE cells. The results indicated the time-dependent and concentration-dependent cytotoxicity of Fe3O4/GO. Meanwhile, exposure to Fe3O4/GO nanomaterials increased reactive oxygen species (ROS) levels，calcium ions levels, and oxidative stress in mitochondria produced by these nanomaterials activated Caspase-9 and Caspase-3, ultimately leading to cell apoptosis.